Yet another small brown frog from high altitude on the Marojejy Massif, northeastern Madagascar (Anura: Mantellidae) - Scherz, Mark D.; Razafindraibe, Jary H.; Rakotoarison, Andolalao; Dixit, Nadi M.; Bletz, Molly C.; Glaw, Frank; Vences, Miguel (Zootaxa, 2017)
Madagascar hosts a high diversity of small brown frogs. In this paper, we add another one by describing Gephyromantis (Duboimantis) tohatra sp. nov. The new species is a small brown mantellid frog discovered on a recent expedition to Marojejy National Park in northeastern Madagascar. It is characterised, among other things, by its small size (snout-vent length ~33 mm), an orange to yellowish belly, two dorsolateral ridges, and a distinctive call composed of 7–10 pulsed notes. The new species occurs sympatrically with other members of the subgenus Duboimantis at high altitude (~1700 m above sea level), including its sister species G. schilfi from which it radically differs by advertisement call and by a substantial genetic divergence of 4.3% uncorrected pairwise distance in the mitochondrial 16S rRNA gene. It thus joins the diverse assemblage of Gephyromantis species known from high altitudes on the mountain massifs of northern Madagascar.